Lenalidomide in combination with dexamethasone at first relapse in comparison with its use as later salvage therapy in relapsed or refractory multiple myeloma - Stadtmauer, E.A.; Weber, D.M.; Niesvizky, R.; Belch, A.; Prince, M.H.; San Miguel, J.F.; Facon, T.; Olesnyckyj, M.; Yu, Z.; Zeldis, J.B.; Knight, R.D.; Dimopoulos, M.A. (European Journal of Haematology, 2009)
This subset analysis of data from two phase III studies in patients with relapsed or refractory multiple myeloma (MM) evaluated the benefit of initiating lenalidomide plus dexamethasone at first relapse. Multivariate analysis showed that fewer prior therapies, along with β2-microglobulin (≤2.5 mg/L), predicted a better time to progression (TTP; study end-point) with lenalidomide plus dexamethasone treatment. Patients with one prior therapy showed a significant improvement in benefit after first relapse compared with those who received two or more therapies. Patients with one prior therapy had significantly prolonged median TTP (17.1 vs. 10.6 months; P = 0.026) and progression-free survival (14.1 vs. 9.5 months, P = 0.047) compared with patients treated in later lines. Overall response rates were higher (66.9% vs. 56.8%, P = 0.06), and the complete response plus very good partial response rate was significantly higher in first relapse (39.8% vs. 27.7%, P = 0.025). Importantly, overall survival was significantly prolonged for patients treated with lenalidomide plus dexamethasone with one prior therapy, compared with patients treated later in salvage (median of 42.0 vs. 35.8 months, P = 0.041), with no differences in toxicity, dose reductions, or discontinuations despite longer treatment. Therefore, lenalidomide plus dexamethasone is both effective and tolerable for second-line MM therapy and the data suggest that the greatest benefit occurs with earlier use. © 2009 Blackwell Munksgaard.
Keywords: Lenalidomide; multiple myeloma; relapse; Survival; Time to progression